Criminal Law Policy in Indonesia Regarding the Distribution of Pornographic Videos on Social Media - Fajar Sitorus; Herlina Manullang; July Esther (International Journal of Law and Society, 2025)
The objective of this study is to evaluate the effectiveness of criminal law policies in Indonesia in addressing the dissemination of pornographic videos on social media. The spread of pornographic videos on social media has become a serious issue in Indonesia, affecting societal morality, particularly among the younger generation. This study aims to analyze the criminal law policies implemented in Indonesia to combat the distribution of pornographic videos through social media platforms. Social media refers to tools or platforms used for communication via networks. This research adopts a normative approach by analyzing relevant regulations, such as the Electronic Information and Transactions (ITE) Law and criminal laws governing pornography. The findings indicate that while several regulations address the dissemination of pornographic content, the effective implementation of these laws remains limited. Challenges include a lack of legal awareness, difficulties in enforcing laws in the digital realm, and weak coordination among law enforcement agencies. Therefore, this study recommends strengthening policies, enhancing public education on the negative impacts of pornography dissemination, and improving the capacity of law enforcement officers to tackle cybercrimes.